Spiritual Intelligence of Nurses in Inpatient Room of Santa Elisabeth Hospital Medan 2022 - Sinurat, Samfriati; Pakpahan, Rotua Elvina; Harefa, Rahmat Putra Budiman (International Journal on Health and Medical Sciences, 2023)
Spiritual intelligence is a framework for identifying, organizing skills and work needed to develop individual abilities to solve problems and achieve goals. A nurse as a service provider to patients needs to develop her spiritual intelligence as the main key to improve the quality of her performance. The purpose of the study was to identify the extent of the spiritual intelligence of nurses in inpatient ward of Santa Elisabeth Hospital Medan 2022. The research method used is descriptive research. The sampling technique is total sampling technique, with a total sample of 91 respondents. Collecting data using a nurse's spiritual intelligence questionnaire. The results showed that the level of spiritual intelligence of nurses in inpatient room of Santa Elisabeth Hospital Medan 2022, the largest spiritual intelligence are 87 respondents (95.6%), and moderate spiritual intelligence are 4 respondents (4.4%). With the results of this study, it is expected that the respondents will continue to get better or have higher intelligence, which can be seen in the attitude and behavior of excellent service so that the quality of service is getting better at the Santa Elisabeth Hospital in Medan, so that the patients served will be satisfied with the quality of their services.